Food security: current challenges - Friedrich, Theodor (Cuban Journal of Agricultural Science, 2016)
Food security exits when “all people have, all the time, physical, social and economic access to enough, innocuous and nutritive food for satisfying their daily energy needs and food preferences, in order to have an active and healthy life”. This way, food security has four main bases: 1. Physical availability of food 2. Economical and physical access to food 3. Appropriate and healthy use of food 4. Stability of these factors over time